2015
DOI: 10.1680/macr.14.00117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autoclave curing on hydration of anhydrite in CFBC fly ash

Abstract: Circulating fluidised bed combustion (CFBC) fly ash contains plenty of anhydrite, so it is important to investigate the hydration behaviour of the anhydrite for the reutilisation of the ash in autoclaved products including autoclaved aerated concrete. X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray spectroscopy were used to study the effect of curing conditions on the hydrates and existence form of the anhydrite in CFBC fly ashcement clinker pastes. Results show that autoclave curin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Anhydrite is formed from the desulfurization process, while mullite is generated from the clay minerals when the temperature exceeds 1000°C. This is consistent with the findings reported in the literatures (Sheng et al 2012;Song et al 2015). Figure 2 shows the SEM images of the CFBC ashes (asreceived) and the PCC fly ash.…”
Section: Methodssupporting
confidence: 91%
“…Anhydrite is formed from the desulfurization process, while mullite is generated from the clay minerals when the temperature exceeds 1000°C. This is consistent with the findings reported in the literatures (Sheng et al 2012;Song et al 2015). Figure 2 shows the SEM images of the CFBC ashes (asreceived) and the PCC fly ash.…”
Section: Methodssupporting
confidence: 91%
“…Song et al [34] found that the maximum bulk density and compressive strength of AAC containing FBCFA are higher than those of AAC containing PCC fly ash, and the volume stability of AAC containing FBCFA is superior to that of AAC containing PCC fly ash. Song et al [124] confirmed that autoclave curing can effectively limit the expansion of anhydrite in FBCFA. Wang et al [19] used metallic aluminum in MSWI bottom ash to make AAC that uses FBCFA.…”
Section: Aerated Concretementioning
confidence: 97%
“…It also contains a reactive mineral phase, which may be represented by pozzolanic properties of FBC fly ash. Moreover, FBC fly ash usually has a high alumina, iron oxide and calcium oxide content [19], [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%